Eco-innovation and emissions trading: A sector analysis for European countries - Silva, P.; Alves, M. R.; Meireles, M.; Madaleno, M. (International Journal of Sustainable Energy Planning and Management, 2021)
This article aims to assess the impact of a specific regulation, namely the European Union emission trading system (EU-ETS) on the Eco-Innovation (EI) activities of the companies, to evaluate its effectiveness in changing the companies’ environmental behavior. It also intends to empirically examine whether the EU-ETS and its ‘stringency’ are significantly related to EI, taking into account both the internal and external factors that might be correlated with EI. To this end, we develop a cross-sectional framework using the Community Innovation Survey (CIS) data and create a stringency indicator for the period between 2012-2014 for 13 European countries. We found that the EU-ETS has limited and some controversial effects. Furthermore, technology policies emerge as an important element of the policy mix complementing climate policy. Based on our findings, we make recommendations for policymakers on how to improve the existing policy mix.